ADP inhibition of myosin V ATPase activity. - De La Cruz, E M (2000)
The kinetic mechanism of myosin V is of great interest because recent evidence indicates that the two-headed myosin V molecule functions as a processive motor, i.e., myosin V is capable of moving along an actin filament for many catalytic cycles of the motor without dissociating. Three recent publications assessing the kinetics of single-headed myosin V provide different conclusions regarding the mechanism, particularly the rate-limiting step of the cycle. One study (, Proc. Natl. Acad. Sci. USA. 96:13726-13731) identifies ADP release as the rate-limiting step and provides a kinetic explanation for myosin V processivity. The others (, J. Biol. Chem. 274:27448-27456;, J. Biol. Chem. 275:4329-4335) do not identify the rate-limiting step but conclude that it is not ADP release. We show experimental and simulated data demonstrating that the inconsistencies in the reports may be due to difficulties in the measurement of the steady-state ATPase rate. Under standard assay conditions, ADP competes with ATP, resulting in product inhibition of the ATPase rate. This presents technical problems in analyzing and interpreting the kinetics of myosin V and likely of other members of the myosin family with high ADP affinities.